2007
DOI: 10.1007/s00234-007-0275-4
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MR imaging (DWI) in the evaluation of epidural spinal lesions

Abstract: Although not statistically significant due to the small patient sample, our results clearly show a tendency toward decreased diffusivity in neoplastic lesions with higher cellularity. The data from our study suggest that DWI is a feasible and potentially useful technique for the evaluation of epidural lesions that cause spinal cord compression on a per-patient basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…Animal studies notably showed that axial and radial diffusivities are good predictors of axonal loss and demyelination, respectively (Budde et al, 2007). DTI has been applied to assess the severity of the spinal cord injury (Agosta et al, 2007;Budde et al, 2007;Cohen-Adad et al, 2008a;DeBoy et al, 2007;Deo et al, 2006;Ducreux et al, 2007;Ellingson et al, 2008;Fujiyoshi et al, 2007;Kim et al, 2007;Lammertse et al, 2007;Nevo et al, 2001;Ohgiya et al, 2007;Plank et al, 2007;Ries et al, 2000;Schwartz et al, 2005;Shen et al, 2007;Thurnher and Bammer, 2006;Valsasina et al, 2005;Vargas et al, 2007). As an extension to DTI, high angular resolution diffusion imaging (HARDI) and Q-Ball imaging (QBI) can represent more than one diffusion direction, thereby alleviating limitations of the diffusion tensor in presence of crossing fibers (Tuch, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Animal studies notably showed that axial and radial diffusivities are good predictors of axonal loss and demyelination, respectively (Budde et al, 2007). DTI has been applied to assess the severity of the spinal cord injury (Agosta et al, 2007;Budde et al, 2007;Cohen-Adad et al, 2008a;DeBoy et al, 2007;Deo et al, 2006;Ducreux et al, 2007;Ellingson et al, 2008;Fujiyoshi et al, 2007;Kim et al, 2007;Lammertse et al, 2007;Nevo et al, 2001;Ohgiya et al, 2007;Plank et al, 2007;Ries et al, 2000;Schwartz et al, 2005;Shen et al, 2007;Thurnher and Bammer, 2006;Valsasina et al, 2005;Vargas et al, 2007). As an extension to DTI, high angular resolution diffusion imaging (HARDI) and Q-Ball imaging (QBI) can represent more than one diffusion direction, thereby alleviating limitations of the diffusion tensor in presence of crossing fibers (Tuch, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…The peak incidence of spinal meningiomas is in the fifth and sixth decades with there being an almost ten to one predilection for females. In the spine, meningiomas are thought to arise from the denticulate ligaments and more than 95% are classified as WHO Grade I [3]. Their extradural component is most commonly related to extension from an intradural mass.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration for lymphoma led to a repeat MRI with diffusion restriction, as prior studies have shown the utility of diffusion-weighted imaging (DWI) in the assessment of spinal lymphoma and other highly cellular tumors [2-3]. The tumor demonstrated marked restriction, supporting a possibility of lymphoma (Figure 2).…”
Section: Case Presentationmentioning
confidence: 92%
“…To allow accurate evaluation of tumour extension in cervical spine, it is of great importance to perform proper imaging. Currently, magnetic resonance imaging (MRI) provides excellent information to assess tumour extension in soft tissue [13,14]. Moreover, it provides images which allow surgeon to differentiate whether intra-spinal or nerve root compression is caused by tumour itself or edema.…”
Section: Clinical Presentation and Imagingmentioning
confidence: 99%